Which peptic ulcer patients bleed?. Issue 1 (January 1988) - Matthewson, K; Pugh, S; Northfield, T C
Abstract : In order to identify factors associated with peptic ulcers which present with bleeding rather than with pain, we have prospectively evaluated patient and endoscopic features in 139 consecutive patients presenting with acute bleeding and 74 presenting with pain found to have peptic ulceration at endoscopy. Patients with bleeding were more likely to have taken non-steroidal anti-inflammatory drugs within the preceding four weeks (58% v 18%, p less than 0.001). They were older (66 v 51 years, p less than 0.001), more likely to have had a previous ulcer complication (21% v 1%, p less than 0.001), and to have an ulcer diameter greater than 20 mm (27% v 6%, p less than 0.05). The presence of one or more of these features in a patient who develops a peptic ulcer appears to be associated with a greater likelihood of presentation with a gastrointestinal haemorrhage.